Rancang Bangun Sistem Presensi Pegawai Menggunakan Pintu Otomatis Berbasis NFC (Near Field Communication) - Kusnandar Kusnandar; Ni Ketut Hariyawati Dharmi; Andika Dwi Naviandi; Yusuf Nugraha (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
The attendance system is considered to be able to assist an agency in providing information about a person's attendance schedule. The attendance system can also be used as an effective tool for implementing discipline in an agency because, in this attendance system, we can see the difference between people's discipline through the timeliness of attendance that has been determined at each of these agencies. In designing this system the method used is NFC (Near Field Communication) where this system can be used to help record someone's attendance schedule. The hardware used is a door lock solenoid, and personal computer devices, while the software used is Wemos D1 Mini. For recording the database used is MySql. The results of presence system using NFC using the Key Door Lock method have a very high level of accuracy for reading an identity card. It can be seen from the data that has been collected that the accuracy of reading an identity card by an NFC reader shows that there is no error or error. The results of response time check test on the NFC reader reading can be proven by formula, where average time value of response time check test is 0.67 minutes.